Writing instruction to support literacy success - Ortlieb, Evan; Cheek, Earl H.; Verlaan, Wolfram (Literacy research, practice and evaluation ;, 2016)
In recent years there has been a universal increase in expectations for academic writing alongside high-stakes tests, as students must master writing for pragmatic purposes including argumentative papers, dialogic narratives, and even research reports. All the while, research related to how to effectively prepare these students for success has been stymied with an over-emphasis on other areas of literacy. This volume features prominent international researchers who share their evidence-based successes partnering with teachers in K-12 classrooms, with particular emphasis on teaching writing products and processes in a digital age. As a result of its up-to-date focus on both print and digital literacies, the book will have wide readership amongst educators who work in the early childhood, elementary, middle, and high school years.